Towards rotation sensing with a single atomic clock - Fernholz, Thomas; Stevenson, Robin; Hush, Michael R.; Lesanovsky, Igor; Bishop, Thomas; Gentile, Fabio; Jammi, Sindhu; Pyragius, Tadas; Bason, Mark G.; Mas, Hector; Pandey, Saurabh; Vasilakis, Georgios; et al. (SPIE, 2016)
We discuss a scheme to implement a gyroscopic atom sensor with magnetically trapped ultra-cold atoms. Unlike standard light or matter wave Sagnac interferometers no free wave propagation is used. Interferometer operation is controlled only with static, radio-frequency and microwave magnetic fields, which removes the need for interferometric stability of optical laser beams. Due to the confinement of atoms, the scheme may allow the construction of small scale portable sensors. We discuss the main elements of the scheme and report on recent results and efforts towards its experimental realization.